Investigation of Echinococcus multilocularis in Environmental Definitive Host Feces in the Asian and the European Parts of Turkey - Gürler, Ali Tümay; Gori, Francesca; Bölükbas¸, Cenk Soner; Umur, Şinasi; Açıcı, Mustafa; Deplazes, Peter (Frontiers in Veterinary Science, 2018)
A study was carried out to investigate the presence of Echinococcus multilocularis in red foxes (Vulpes vulpes) in two regions of Turkey, central Anatolia (in Asia Minor) and Thrace (in the European part of Turkey). A total of putative 405 fox faeces were collected from central Anatolia (186 specimens in 59 locations) and from Thrace (219 specimens in 114 locations). All samples were examined by the flotation and sieving method for taeniid eggs and positive and putative samples were further analysed by multiplex-PCR. In seven samples from three locations in central Anatolia (5.1%) and in one (0.9%) from Thrace, E. multilocularis DNA was amplified and this result was confirmed with another PCR specific for E. multilocularis. In addition, E. granulosus s.l. was found in two (0.5%) of the samples. Although AE is known as a serious zoonosis in Turkey, this is the first field study detecting E. multilocularis in collected faecal samples documenting the environmental contamination with eggs of this zoonotic parasite.